HAK KONSUMEN DAN KEWAJIBAN PELAKU USAHA ANALISIS PUTUSAN MAHKAMAH KONSTITUSI NOMOR 65/PUU-XIII/2015 - Nabila Ika Saputri; Burham Pranawa; Tegar Harbriyana Putra (Fakultas Hukum Universitas Boyolali, 2020)
he Indonesian state is based on the state foundation, namely Pancasila which is contained in the 1945 Constitution in the era of economic democracy for national development to achieve a prosperous economy through the direction of policies that can support the national government program, one of which is through the economic sector assisted by tools and knowledge technology. So, it is expected to create and produce a balance between producers and consumers. In practice, the consumer is involved in losses incurred by the business actor / producer. The purpose of the study was to find out the legal bases that were found from the consideration of the panel of judges in deciding Case No. 65 / PUU-XIII / 2015 concerning consumer protection and the legal consequences of breaking up. This type of research is a type of normative legal research through secondary data sources consisting of , secondary, primary and tertiary legal data. The results of the research are the bases of the legal results of the judges' considerations in deciding Decision No. 65 / PUU-XIII / 2015 of the law on Consumer Protection, namely legal considerations from the panel of judges, namely juridical, philosophical and sociological aspects. As a result of the Decision of the Constitutional Court Number 65 / PUU-XIII / 2015, namely the Article submitted by the petitioners is declared still valid and does not contradict the 1945 Constitution both from its formation and material and the applicant is required to obey the Decision. His advice to people who have problems with business actors hope that they can comprehend complete the articles in the law that will be tested and the government and law enforcement officials regarding the constitution, to disseminate information to people who do not know the procedural procedures in the Constitutional Court. Negara Indonesia berdasarkan dasar negara yaitu Pancasila yang terdapat dalam Undang-Undang Dasar Tahun 1945 dalam era demokrasi ekonomi untuk pembangunan nasional mencapai ekonomi menjadi sejahtera melalui arah kebijakan-kebijakan yang dapat mendukung dari program pemerintahan nasional salah satunya melalui bidang ekonomi dibantu dengan alat dan ilmu teknologi. Sehingga, diharapkan dapat menciptakan dan menghasilkan keseimbangan antara produsen dan konsumen. Pada prakteknya dari pihak konsumen terlibat kerugian yang dilakukan pihak pelaku usaha/ produsen. Tujuan Penelitian adalah mengetahui dasar- dasar hukum yang terdapat dari pertimbangan majelis hakim dalam memutus Perkara No. 65/PUU-XIII/2015 tentang perlindungan konsumen dan akibat hukum dari putusanya. Jenis penelitiannya merupakan jenis penelitian hukum normatif melalui sumber data-data sekunder yang terdiri dari data bahan hukum sekunder, primer dan bahan hukum tertier. Hasil dari penelitian adalah dasar –dasar dari hukum pertimbangannya majelis hakim dalam memutus perkara No. 65/PUU-XIII/2015 tentang Perlindungan Konsumen yaitu pertimbangan hukumnya dari majelis hakim yaitu aspek yuridis, filosofis dan sosiologis. Akibat dari Putusan Mahkamah Konstitusi Nomor 65/PUU-XIII/2015 yaitu Pasal yang diajukan para pemohon dinyatakan masih tetap berlaku dan tidak bertentangan UUD 1945 baik dari pembentukan dan materinya serta pemohon diwajibkan mentaati Putusan tersebut. Sarannya ke masyarakat yang mempunyai permasalahan terhadap pelaku usaha harap dapat memahami secara menyeluruh atas Pasal di UU yang akan diujikan dan pemerintah dan aparat penegak hukum mengenai konstitusional, untuk melakukan sosialisasi ke masyarakat yang tidak mengetahui tata beracara di Peradilan Konstitusi.